THE CONTROLLER AND PENSION PLANS. - Norton, Roger L. (The Accounting Review, 1953)
Organized plans for providing old-age benefits first appeared in Great Britain around 1850. At the present time pension plans are being initiated in all types of industries and institutions. Each may be slightly different from the others in form but the main theme is preserved. The emphasis is upon benefits to the workers. The outlook for the future is that more and more benefit plans will be inaugurated in progressive business firms. The board of directors as the voice of the stockholders is usually the first group to decide to investigate the possible adoption of a pension plan. However in some cases the actual consent of the stockholders may be necessary because of charter provisions or by-laws. After deciding to initiate a pension plan, a firm must consider the manner through which it will set aside and pay the benefits derived from the plan. Several types of plans are open to the firm, but the choice depends on the conditions existing within the particular company. For small businesses the individual policy plan may be advantageous because the continuity of employment is generally greater and participation can be more selective.